APAKAH HYPNOBIRTHING DAPAT MENURUNKAN NYERI PERSALINAN ?: SYSTEMATIC LITERATURE REVIEW - Rianti Fitriani; Lisa Trina Arlym; Yocki Yuanti (JURNAL KESEHATAN DAN KEBIDANAN, 2022)
Hypnobirthing is a relaxation method with slow breathing patterns so that endorphins are slowly released by the body. This study aims to identify the effect of hypnobirthing on labor pain in the active phase of the 1st stage. The research method was a systematic literature review by identifying all published literature using relevant keywords. The selected articles are those published in the last 10 years which are full text, then selected based on the title and abstract which in the end found 5 articles that met the inclusion criteria and had high quality. The results showed that there was a significant effect of hypnobirthing on labor pain. Mothers who do hypnobirthing starting in pregnancy get more benefits than hypnobirthing starting during the first stage of labor. Thus, hypnobirthing should be an option in reducing labor pain in addition to other benefits.